Effect of Benzyladenine (BA) and Thidiazuron (TDZ) Application on the Bud Emergence and Seedling Uniformity of Sugarcane Setts - Puput Ninggariawan; Yusnita Yusnita; Dwi Hapsoro; Kukuh Setiawan; Rusdi Evizal (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Benzyladenine (BA) and thidiazuron (TDZ) are widely recognized as plant growth regulators that can stimulate bud activation in sugarcane. However, information regarding the synergistic effects of BA and TDZ, particularly in field-level sett treatment, remains limited. This study aimed to evaluate the effect of benzyladenine (BA) and its combination with thidiazuron (BA+TDZ) on bud emergence and seedling uniformity of sugarcane (Saccharum officinarum L.) setts. The experiment was arranged in a randomized complete block design with three replications, involving four sugarcane varieties (GP 99-8009, GP 05-17, GP 08-132, and TC 09) and three treatments: control (0 ppm), BA 50 ppm, and BA 50 ppm + TDZ 5 mg/L. Each experimental unit consisted of 20 buds from 10 two-budded setts. The results showed that the combination of BA 50 ppm + TDZ 5 mg/L significantly enhanced bud emerging percentage, plant height, and fresh and dry stem weights compared to BA alone and control. Variety had no significant effect, and no interaction was observed between variety and hormonal treatment. It can be concluded that the combination of BA and TDZ effectively stimulates bud emergence and early growth of sugarcane, indicating its potential use in seedling establishment.